Positive electrode active material, method of preparing same, and positive electrode and rechargeable lithium battery including same
By uniformly coating the aluminum layer on the surface of the positive electrode active material of lithium nickel-manganese composite oxide, forming a fiber-shaped structure, the problems of shortage of cobalt supply and poor performance under high temperature and high voltage are solved, and a lithium battery with high capacity and long cycle life is achieved.
Patent Information
- Application Number
- CN202411527899.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-31
- Filing Date
- 2024-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The positive electrode active substance used in existing rechargeable lithium batteries contains rare metal cobalt, which leads to shortage of supply, and under high voltage and high temperature conditions, structural stability and cycle life characteristics are difficult to ensure.
A positive electrode active material based on layered lithium nickel-manganese composite oxide is used, and an aluminum layer is uniformly coated on its surface to form a fiber-shaped structure to improve the performance and life of the battery.
Through the application of aluminum coating, the performance of lithium nickel manganese composite oxides at high temperatures and high voltages is improved, and the high capacity and long cycle life characteristics are ensured, while reducing the amount of gas generated and improving the safety of the battery.
Smart Images

Figure CN119920864A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a positive electrode active material, a preparation method thereof, a positive electrode including the positive electrode active material, and a rechargeable lithium battery. Background Art
[0002] Portable information devices (such as cellular phones, laptop computers, smart phones, etc.) and / or electric vehicles have used rechargeable lithium batteries with relatively high energy density and easy portability as driving power sources. Recently, research has been actively conducted to use such rechargeable lithium batteries with relatively high energy density as driving power sources for hybrid vehicles and / or electric vehicles, or as power storage power sources for power storage stations and / or power walls.
[0003] Various positive electrode active materials have been studied to realize rechargeable lithium batteries suitable for these applications. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and lithium cobalt oxides are mainly used as positive electrode active materials. However, although the demand or expectation for rechargeable lithium batteries with relatively large size, high capacity and / or high energy density has increased recently, it is expected that the supply of positive electrode active materials containing rare metal cobalt will be in short supply (severe shortage). For example, because cobalt is expensive and there are not many remaining reserves, it is necessary or desirable to develop positive electrode active materials that exclude (e.g., do not include or substantially do not include) cobalt or use cobalt in a reduced amount. Summary of the invention
[0004] Aspects according to some embodiments relate to a positive electrode active material including a lithium nickel manganese composite oxide and implementing (eg, including) a substantially uniform aluminum coating to improve performance of a rechargeable lithium battery at high temperature and high voltage and ensure high capacity and long cycle life characteristics.
[0005] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented embodiments of the disclosure.
[0006] In one or more embodiments, the positive electrode active material includes: core particles, (e.g., each) including a layered lithium nickel manganese composite oxide (hereinafter referred to as "lithium nickel manganese composite oxide") having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese composite oxide; and a coating on the surface of (each of) the core particles and containing Al, wherein the amount of Al in the coating is about 0.5 mol% to about 1.5 mol% based on 100 mol% of the total metals other than lithium in the positive electrode active material, and the coating contains a fiber-shaped structure (e.g., in the form of fibers, having a fibrous structure, etc.).
[0007] In one or more embodiments, a method for preparing the aforementioned positive electrode active material includes: (i) preparing core particles, the core particles (e.g., each) including a layered lithium nickel manganese composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of total metals other than lithium in the layered lithium nickel manganese composite oxide and having a residual lithium content (e.g., amount) of about 0.15 wt% to about 0.25 wt% on the surface of the core particles (each of which); (ii) adding aluminum sulfate to an aqueous solvent and mixing to prepare a coating solution; (iii) adding the core particles to the coating solution and mixing to prepare a mixed solution having a pH of about 5.5 to about 7.5, and (iv) removing the aqueous solvent from the mixed solution, drying the resulting product and heat-treating it to obtain a positive electrode active material.
[0008] In one or more embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material.
[0009] In one or more embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and electrolyte.
[0010] The positive electrode active material according to one or more embodiments can maximize or increase capacity while minimizing or reducing production costs to ensure long cycle life characteristics and improve high voltage characteristics and high temperature characteristics. If (for example, when) the positive electrode active material is applied to a rechargeable lithium battery (when), a high initial charge / discharge capacity and efficiency can be achieved under high voltage operating conditions, a long cycle life characteristic can be achieved, and the amount of gas generated due to high voltage and high temperature operation can be effectively suppressed or reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The accompanying drawings are included to provide a further understanding of the present disclosure and are incorporated in and constitute a part of this specification. The accompanying drawings illustrate embodiments of the present disclosure and together with the description serve to explain the principles of the present disclosure. In the accompanying drawings,
[0012] Figure 1 is a schematic illustration of a cylindrical battery according to some embodiments.
[0013] Figure 2 is a schematic illustration of a prismatic battery according to some embodiments.
[0014] Figure 3 is a schematic illustration of a pouch-type or similar battery according to some embodiments.
[0015] Figure 4is a schematic illustration of a pouch-type or similar battery according to some embodiments.
[0016] Figure 5 is a scanning electron microscope (SEM) image showing the surface of the coated product according to Example 1.
[0017] Figure 6 To show Figure 5 A magnified image of a portion of .
[0018] Figure 7 An energy dispersive X-ray spectroscopy (EDS) analysis image showing a cross section of a positive electrode active material according to Example 1, wherein the Al element is highlighted.
[0019] Figure 8 : is a SEM image showing the surface of the coated product according to Example 2.
[0020] Fig. 9 : is a SEM image showing the surface of the coated product according to Example 3.
[0021] Fig.10 : is a SEM image showing the surface of the coated product according to Example 4.
[0022] Fig.11 An EDS analysis image showing a cross section of the positive electrode active material according to Comparative Example 1, in which Al is highlighted.
[0023] Fig.12 : is a SEM image showing the surface of the coated product according to Comparative Example 2.
[0024] Fig.13 is a SEM image showing the surface of the coated product according to Comparative Example 3-1.
[0025] Fig.14 is a SEM image showing the surface of the coating product according to Comparative Example 3-2.
[0026] Fig.15 is a SEM image showing the surface of the coating product according to Comparative Example 3-3.
[0027] Fig.16 : is a SEM image showing the surface of the coated product according to Comparative Example 4.
[0028] Fig.17 : is a SEM image showing the surface of the coated product according to Comparative Example 5.
[0029] Fig.18A bar graph showing the ratio of the Al content (e.g., amount) on the surface of the core particles to the total content (e.g., amount) of Ni, Mn and Al (Al / (Ni+Mn+Al)) as a result of energy distribution energy dispersive X-ray spectroscopy (EP-EDS) analysis of the coating products according to Examples 1 to 3 and Comparative Examples 1, 2 and 3-3.
[0030] Reference numerals
[0031] 100: Rechargeable lithium battery 10: Positive electrode
[0032] 11: Positive electrode lead lug 12: Positive electrode terminal
[0033] 20: Negative electrode 21: Negative electrode lead lug
[0034] 22: Negative electrode terminal 30: Separator
[0035] 40: electrode assembly 50: shell
[0036] 60: Sealing member 70: Electrode terminal piece
[0037] 71: Positive electrode terminal tab 72: Negative electrode terminal tab DETAILED DESCRIPTION
[0038] Hereinafter, specific embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the present disclosure may be implemented in many different forms and should not be construed as limited to the example embodiments set forth herein.
[0039] The terms used herein are only used to describe the embodiments and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.
[0040] As used herein, the term "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of components.
[0041] In this document, it should be understood that terms such as “comprises,” “includes,” or “have” are intended to indicate the presence of implemented features, quantities, (e.g., actions or tasks) steps, elements, and / or their (e.g., any appropriate) combinations, but it does not exclude the possibility of the presence or addition of one or more other features, quantities, (e.g., actions or tasks) steps, elements, and / or their (e.g., any appropriate) combinations.
[0042] In the accompanying drawings, the size (e.g., thickness) of layers, films, panels, regions, etc. is exaggerated for clarity, and the same reference numerals represent the same elements throughout, and a repeated description thereof may not be provided in the specification. It will be understood that if (e.g., when) an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it may be directly on the other element (such as a layer, film, region, or substrate), or there may also be intervening elements. In contrast, if (e.g., when) an element (such as a layer, film, region, or substrate) is referred to as being "directly on" another element (such as a layer, film, region, or substrate), there are no intervening elements.
[0043] In addition, the term "layer" as used herein includes not only a shape formed on the entire surface if (for example, when) viewed from a plan view, but also a shape formed on a partial surface.
[0044] The average particle size can be measured by an appropriate method (e.g., known to those skilled in the art), for example, by a particle size analyzer, or by a transmission electron microscope image or a scanning electron microscope image. In one or more embodiments, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise specified, the average particle size (D 50 ) may refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution. As used herein, if (for example, when) no other definition is provided, the average particle diameter (D 50 ) refers to the diameter of particles with a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image. And, unless otherwise defined, in the present disclosure, if (for example, when) the particles are spherical (when), the term "particle size" refers to the average diameter, and if (for example, when) the particles are non-spherical (when), the term "particle size" refers to the average major axis length.
[0045] In this document, the term "or" is not to be interpreted as an exclusive meaning, for example, "A or B" means A, B, A+B, etc.
[0046] The term "metal" as used herein refers to common metals, transition metals, and metalloids (semimetals).
[0047] Positive electrode active material
[0048] In one or more embodiments, the positive electrode active material includes: core particles (e.g., core particles in the form of core particles), (e.g., each) including a layered lithium nickel manganese composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of the total metal other than lithium in the layered lithium nickel manganese composite oxide; and a coating located on the surface of (each of) the core particles and containing Al. Based on 100 mol% of the total metal other than lithium in the positive electrode active material, the Al content (e.g., amount) of the coating is about 0.5 mol% to about 1.5 mol%, and the coating contains a fiber-shaped structure (e.g., in the form of fibers, having a fibrous structure, etc.).
[0049] Since the price of rare metal cobalt has risen sharply recently, it is necessary to develop a positive electrode active material that excludes (does not include) cobalt or has a reduced cobalt content (e.g., amount). Among them, positive electrode active materials with olivine crystal structure (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium manganese iron phosphate (LMFP), etc.) and / or positive electrode active materials with spinel crystal structure (such as lithium manganese oxide (LMO), etc.) are limited in achieving high capacity due to the small amount of lithium available in their structure. Due to the high amount of available lithium in the structure, the layered lithium nickel manganese positive electrode active material has excellent or suitable capacity and efficiency characteristics, making it suitable as a material for high-capacity batteries. However, as cobalt, which plays a key role in the layered structure, is removed, the structural stability is reduced, the resistance is increased, and it becomes difficult to ensure long cycle life characteristics. In addition, removing cobalt from the layered lithium nickel manganese positive electrode active material can lead to the problem of accelerating the side reaction with the electrolyte under high voltage and high temperature conditions, thereby causing increased gas generation and deterioration of cycle life characteristics.
[0050] The method according to one or more embodiments may strengthen the surface of a lithium nickel manganese-based positive electrode active material by uniformly (eg, substantially uniformly) coating it with aluminum, thereby maintaining a stable structure even at a high voltage and achieving long cycle life characteristics.
[0051] Nuclear particles
[0052] The core particles include lithium nickel manganese composite oxides. Based on 100mol% of the total metals other than lithium in the lithium nickel manganese composite oxide, the nickel content (e.g., amount) may be greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If the nickel content (e.g., amount) satisfies the above range, even if the cobalt content (e.g., amount) is reduced, high capacity can be achieved and structural stability can be increased.
[0053] Based on 100 mol% of the total metals other than lithium in the lithium nickel manganese composite oxide, the manganese content may be greater than or equal to about 10 mol%, for example, greater than or equal to about 15 mol%, for example, about 15 mol% to about 40 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30 mol%. If the manganese content (e.g., amount) satisfies the above range, the positive electrode active material can improve structural stability while achieving high capacity.
[0054] Lithium nickel manganese composite oxides may be, for example, lithium nickel manganese aluminum composite oxides further including aluminum in addition to nickel and manganese. If the lithium nickel manganese composite oxide includes aluminum, it is suitable for or advantageous to maintain a stable layered structure even if the cobalt element is excluded from the structure. The aluminum content (e.g., amount) of the total metal other than lithium based on 100 mol% of the lithium nickel manganese composite oxide may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, such as greater than 0 mol% and less than or equal to 3 mol%, such as about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 2.5 mol%. If the aluminum content (e.g., amount) satisfies the above range, even if cobalt is excluded, a stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed or reduced, and the long cycle life characteristics of the positive electrode active material can be achieved.
[0055] According to one or more embodiments, the concentration of aluminum in the core particle may be substantially uniform. In some embodiments, there may be no concentration gradient of aluminum from the center to the surface in the core particle, or the aluminum concentration of the inner part of the core particle is neither higher than nor lower than the aluminum concentration of the outer part, and the aluminum may be uniformly distributed in the core particle. This may be a structure obtained by using aluminum raw materials during precursor production and not additionally doping aluminum during the synthesis of the core particle, thereby using nickel-manganese-aluminum composite hydroxides as precursors to synthesize lithium-nickel-manganese-aluminum composite oxides. The core particles (e.g., each) may be in the form of secondary particles in which a plurality of primary particles are aggregated, and the aluminum content (e.g., amount) inside the primary particles may be the same (or substantially the same) or similar, regardless of the position of the primary particles. For example, if a primary particle is selected at a random position in the cross section of the secondary particle, and the aluminum content (e.g., amount) is measured inside the primary particle rather than at its interface (e.g., an interface with another particle), the aluminum content (e.g., amount) can be substantially the same / similar / uniform regardless of the position of the primary particle (i.e., whether the primary particle is near the center of the secondary particle or near its surface). In this structure, even if cobalt is not present or present in a very small amount, a stable layered structure can be maintained, and aluminum byproducts or aluminum aggregates are not generated, thereby all improving the capacity, efficiency, and cycle life characteristics of the positive electrode active material at the same time.
[0056] In some embodiments, the lithium nickel manganese-based composite oxide may be represented by Chemical Formula 1.
[0057] Chemical formula 1
[0058] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1
[0059] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.
[0060] In some embodiments, in Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2. Additionally, Chemical Formula 1 may contain aluminum, in which case, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 may be satisfied, and for example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 may be satisfied.
[0061] In some embodiments, in Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79; 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3; 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019; and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09.
[0062] In some embodiments, the lithium nickel manganese composite oxide may not include (e.g., may exclude) cobalt or may include a small amount of cobalt, and based on the total metals other than lithium in 100 mol% of the lithium nickel manganese composite oxide, the cobalt content (e.g., amount) may be from about 0 mol% to about 0.01 mol%.
[0063] The core particles may be in the form of secondary particles made by aggregating a plurality of primary particles. The secondary particles may be spherical, elliptical, polyhedral, or irregular in shape, and the primary particles may be spherical, elliptical, plate-like, and / or any suitable combination thereof.
[0064] If (e.g., when) the battery is operated under high voltage or high temperature conditions, the core particles are vulnerable to chemical erosion by the components in the electrolyte, and side reactions with the electrolyte may occur, resulting in an increase in the amount of gas generated, thereby deteriorating the battery cycle life and safety. These problems can be solved by introducing a coating according to the embodiments to be described in more detail later.
[0065] Coating
[0066] Based on 100 mol% of the total metal other than lithium in the positive electrode active material, the Al content (e.g., amount) in the coating layer may be about 0.5 mol% to about 1.5 mol%, such as about 0.6 mol% to about 1.4 mol%, about 0.7 mol% to about 1.3 mol%, or about 0.8 mol% to about 1.2 mol%. The Al content (e.g., amount) refers only to the content (e.g., amount) of aluminum included in the coating layer, which is separated from (not included in) the aluminum included in the core particles. The aluminum content (e.g., amount) in the coating layer may be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If (e.g., when) the aluminum content (e.g., amount) in the coating layer satisfies these ranges, the coating layer may have a substantially uniform and thin thickness, which does not increase the resistance of the positive electrode active material, and effectively inhibits or reduces side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under high voltage and high temperature conditions. For example, if the aluminum content (e.g., amount) of the coating is too much (e.g., greater than about 1.5 mol%), a uniform coating may not be formed or the resistance may increase, which may reduce the charge / discharge efficiency and cycle life characteristics, and if the aluminum content (e.g., amount) of the coating is too little (e.g., less than about 0.5 mol%), a coating of suitable or appropriate thickness may not be formed and the effect of inhibiting or reducing side reactions with the electrolyte may be reduced.
[0067] The coating according to one or more embodiments contains a fiber-shaped structure (e.g., in fiber form, with a fibrous structure, etc.). The coating may be, for example, in the form of a grid or a spider web shape. The grid-like coating may be formed on the entire surface of the core particle, and therefore may be described as a coating surrounding the entire surface of the core particle. This is different from a structure in which only a portion of the core particle surface is locally coated.
[0068] The coating can be formed to be very thin and substantially uniform in thickness, while containing a fiber-shaped structure (e.g., in the form of fibers, having a fibrous structure, etc.), so that the positive electrode active material does not increase resistance or reduce capacity (e.g., due to the inclusion of the coating), while improving structural stability, effectively inhibiting side reactions with the electrolyte, reducing the amount of gas generated under high voltage and high temperature conditions, and achieving long cycle life characteristics.
[0069] The coating may have a thickness of about 5 nm to about 200 nm, such as about 10 nm to about 200 nm, about 20 nm to about 200 nm, about 30 nm to about 150 nm, about 40 nm to about 100 nm, or about 50 nm to about 80 nm. If the coating satisfies these thickness ranges, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, scanning electron microscopy (SEM), transmission electron microscopy (TEM), time of flight-secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS) or energy dispersive X-ray spectroscopy (EDS), and for example, the thickness of the coating can be measured by SEM-EDS analysis images of the cross section of the positive electrode active material.
[0070] According to one or more embodiments, the coating may be a thin thickness of several nanometers to several hundred nanometers and uniform (or substantially uniform) in thickness. For example, the deviation of the coating thickness within a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness within a positive electrode active material particle. For example, the deviation of the coating thickness can be calculated by measuring the thickness of about 10 points in the electron microscope image of the cross section of a single positive electrode active material particle to calculate the arithmetic mean, and then the absolute value of the difference between one measurement data and the arithmetic mean is divided by the arithmetic mean and multiplied by 100%. The fact that the deviation or standard deviation of the coating thickness meets the above range refers to a coating of substantially uniform thickness formed in the form of a film (e.g., well) on the surface of the core particle of the positive electrode active material. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte is effectively suppressed or reduced, and the increase in resistance or the decrease in capacity due to the coating can be minimized or reduced.
[0071] The coating may include, for example, a layered aluminum compound, such as, for example, aluminum oxide, lithium aluminum oxide (eg, LiAlO 2 ), and / or (eg, any suitable) combinations thereof.
[0072] In addition to aluminum, the coating may further contain nickel, manganese, and / or (eg, any suitable) combinations thereof.
[0073] In one or more embodiments, on the surface of the positive electrode active material according to one or more embodiments, based on 100at% (atomic percentage) of the total metal other than lithium on the surface of the positive electrode active material, the Al content (e.g., amount) may be about 45at% to about 55at%, and by coating with such a high content (e.g., amount) of Al, the structural stability of the positive electrode active material can be improved. The Al content (e.g., amount) on the surface of the positive electrode active material can be measured, for example, by energy dispersive X-ray spectroscopy (EDS).
[0074] Grain boundary coating part
[0075] In one or more embodiments, during the coating formation process, aluminum may diffuse into the core particles. Accordingly, the positive electrode active material according to one or more embodiments may further include a grain boundary coating portion, which includes aluminum and is arranged on the surface of the primary particles in the inner portion of the secondary particles. In this article, the secondary particle refers to the core particle, and the inner portion of the secondary particle may refer to the entire inner portion except the surface of the secondary particle, or may be a zone of about 60% of the radius of the secondary particle (i.e., the distance from the surface of the secondary particle to the center of the secondary particle) from the center of the secondary particle toward the surface of the secondary particle. The grain boundary coating portion is different from the coating on the surface of the core particle, and refers to the coating portion formed on the surface of the primary particle inside the core particle. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. By forming a grain boundary coating portion, the positive electrode active material can become more structurally stable and its cycle life characteristics can be improved.
[0076] The aluminum content (eg, amount) in the grain boundary coating portion is not particularly limited, and, for example, the aluminum content (eg, amount) in the grain boundary coating portion may be smaller than the aluminum content (eg, amount) in the coating layer.
[0077] In some embodiments, in addition to aluminum, the grain boundary coating portion may also further include nickel, magnesium, yttrium, and / or (eg, any suitable) combinations thereof.
[0078] The average particle size (D 50 ) is not particularly limited, but may be, for example, about 1 μm to about 25 μm, about 5 μm to about 25 μm, about 10 μm to about 25 μm, about 11 μm to about 20 μm, or about 12 μm to about 18 μm. As used herein, if (for example, when) no limitation is otherwise provided, the average particle size (D 50) refers to the diameter of particles with a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image of the positive electrode active material. If the average particle size of the positive electrode active material satisfies the above range, high capacity and long cycle life can be achieved, and it can be suitable for or conducive to forming a coating according to one or more embodiments.
[0079] In addition, in one or more embodiments, the positive electrode active material may not include (e.g., may exclude) sodium. Generally speaking, sodium ions can be used in the preparation process of the positive electrode active material, but according to the preparation method described in more detail later, a core particle having a stable structure and a coating having a substantially uniform thickness can be formed without using sodium ions.
[0080] Method for preparing positive electrode active material
[0081] In one or more embodiments, the method for preparing a positive electrode active material includes: (i) preparing core particles, the core particles (e.g., each) including a layered lithium nickel manganese composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of the total metal other than lithium in the lithium nickel manganese composite oxide and having a residual lithium content (e.g., amount) of about 0.15 wt% to about 0.25 wt% on the surface; (ii) adding aluminum sulfate to an aqueous solvent and mixing to prepare a coating solution; (iii) adding the core particles to the coating solution and mixing to prepare a mixed solution having a pH of about 5.5 to about 7.5; and (iv) removing the aqueous solvent from the mixed solution, drying the resulting product and heat-treating it to obtain a positive electrode active material. The aforementioned positive electrode active material can be prepared by the above method.
[0082] First, a layered lithium nickel manganese composite oxide can be prepared, for example, by mixing a nickel manganese composite hydroxide and a lithium raw material and performing a first heat treatment. The nickel manganese composite hydroxide can be a precursor of a core particle and can be in the form of a secondary particle in which a plurality of primary particles are aggregated. The nickel manganese composite hydroxide (e.g., a nickel manganese aluminum composite hydroxide) can be prepared by a general coprecipitation method.
[0083] In the nickel-manganese composite hydroxide, based on 100mol% of the total metal in the nickel-manganese composite hydroxide, the nickel content (e.g., amount) may be greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If (e.g., when) the nickel content (e.g., amount) satisfies the above range (when), even if the cobalt content (e.g., amount) is reduced, high capacity can be achieved and structural stability can be increased.
[0084] The manganese content (e.g., amount) in the nickel-manganese-based composite hydroxide may be greater than or equal to about 10 mol%, for example, greater than or equal to about 15 mol%, for example, from about 15 mol% to about 40 mol%, from about 15 mol% to about 39 mol%, from about 15 mol% to about 35 mol%, from about 15 mol% to about 30 mol%, or from about 20 mol% to about 30 mol%, based on 100 mol% of total metals in the nickel-manganese-based composite hydroxide.
[0085] In addition, if (for example, when) the nickel-manganese composite hydroxide further contains aluminum (when), the aluminum content (for example, amount) based on 100mol% of the total metal in the nickel-manganese composite hydroxide may be greater than or equal to about 0.1mol%, greater than or equal to about 0.5mol%, or greater than or equal to about 1mol%, for example, about 1mol% to about 3mol%, about 1mol% to about 2.5mol%, about 1mol% to about 2mol%, or about 1mol% to about 1.9mol%. If the manganese and aluminum contents of the nickel-manganese composite hydroxide meet the above respective ranges, high capacity can be achieved, while the structural stability of the positive electrode active material can be increased, and the production price can be reduced to increase economic benefits.
[0086] In the method for preparing a positive electrode active material according to one or more embodiments, when preparing the core particles, aluminum is not additionally doped, but an aluminum raw material can be used to prepare a precursor, so that a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly (e.g., substantially uniformly) dispersed in the structure can be used as a precursor. If (e.g., when) such a precursor is used, the positive electrode active material can stably maintain a layered structure without cobalt despite repeated charging and discharging, and aluminum byproducts or aluminum aggregates may not be formed, thereby improving the capacity and efficiency characteristics and cycle life characteristics of the positive electrode active material.
[0087] In the nickel-manganese composite hydroxide, the cobalt content (e.g., amount) may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, based on 100 mol% of the total metal in the nickel-manganese composite hydroxide. Such a nickel-manganese composite hydroxide may be economical because it avoids or reduces the increase in unit cost caused by cobalt, maximizes or increases capacity, and improves structural stability.
[0088] As an example, the nickel-manganese-based composite hydroxide may be represented by Chemical Formula 2.
[0089] Chemical formula 2
[0090] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2
[0091] In Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, and 0.9≤x2+y2+z2+w2≤1.1, and M 2 It is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr.
[0092] In some embodiments, in Chemical Formula 2, for example, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, and 0≤w2≤0.29.
[0093] The nickel-manganese composite hydroxide may be in the form of particles, and the average particle size (D 50 ) may be about 1 μm to about 25 μm, about 5 μm to about 20 μm, about 10 μm to about 20 μm, about 11 μm to about 18 μm, or about 12 μm to about 15 μm.
[0094] The nickel-manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8, for example, about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2. The first heat treatment can be carried out in an oxygen atmosphere, for example, in a temperature range of about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C for about 2 hours to about 20 hours or about 4 hours to about 12 hours. By the first heat treatment, a lithium nickel-manganese composite oxide can be obtained. The obtained lithium nickel-manganese composite oxide is substantially the same as the lithium nickel-manganese composite oxide described for the core particles in the positive electrode active material section.
[0095] Based on the total weight (100wt%) of the core particles, the core particles containing the layered lithium nickel manganese composite oxide according to one or more embodiments may have a residual lithium content (e.g., amount) ranging from about 0.15wt% to about 0.25wt% on the surface. For example, the content (e.g., amount) of LiOH remaining on the surface of the core particles may be 0.3wt% to about 0.5wt%, and the content (e.g., amount) of Li2CO3 remaining on the surface of the core particles may be about 0.25wt% to about 0.6wt%.
[0096] Because such layered lithium nickel manganese composite oxides may have significantly different residual lithium contents on the particle surfaces and different various characteristics from oxides having different compositions (e.g., lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, lithium cobalt oxides, etc.), it is unlikely or impossible to form a satisfactory coating in the form of a substantially uniform film using a coating method of the related art. The method according to one or more embodiments is capable of coating Al very uniformly (e.g., substantially uniformly) on the particle surfaces of layered lithium nickel manganese composite oxides having the above-mentioned residual lithium content.
[0097] In one or more embodiments, after first preparing a coating solution by adding aluminum sulfate to an aqueous solvent and mixing them, the core particles are added to the coating solution and then mixed with the coating solution to prepare a mixed solution having a pH in the range of about 5.5 to about 7.5. This is a salt dissolution wet coating method and a pre-addition method: first, the salt (coating raw material) is completely dissolved in a solvent, and then the active material particles are added thereto.
[0098] The aqueous solvent may include distilled water, an alcohol solvent, and / or (eg, any suitable) combinations thereof.
[0099] Aluminum sulfate may be the best or appropriate raw material for forming a coating according to one or more embodiments. Based on the final positive electrode active material obtained 100 mol% of the total metal other than lithium (i.e., based on the sum of 100 mol% of the total metal other than lithium in the core particle and the aluminum of the aluminum sulfate), the Al content (e.g., amount) in the aluminum sulfate may be designed to be about 0.5 mol% to about 1.5 mol%, for example, about 0.6 mol% to about 1.4 mol%, about 0.7 mol% to about 1.3 mol% or about 0.8 mol% to about 1.2 mol%. If the Al content (e.g., amount) in the coating is designed within these ranges, the coating may be formed to have a thin and substantially uniform thickness of several to several hundred nanometers, reducing the amount of gas generated by the rechargeable lithium battery under high voltage or high temperature operating conditions, and improving high capacity and long cycle life characteristics.
[0100] Aluminum sulfate is added to the aqueous solvent and mixed for about 1 minute to about 60 minutes, for example, about 3 minutes to about 30 minutes or about 5 minutes to about 10 minutes. In addition, mixing can be carried out at a speed of about 100rpm to about 800rpm (for example, about 200rpm to about 600rpm or about 250rpm to about 500rpm). Under these conditions, aluminum sulfate is completely dissolved in the aqueous solvent to obtain a colorless and transparent coating solution, and the coating solution can be used to effectively form a substantially uniform aluminum coating according to one or more embodiments. The coating solution to complete mixing may have, for example, a pH of about 1.5 to about 3.5 (for example, about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3 or about 2.9 to about 3.2).
[0101] In the process of adding the core particles to the prepared coating solution, the core particles are added thereto while the coating solution is stirred to improve the coating quality.
[0102] In addition, the core particles can be added to the coating solution at a speed of about 30 seconds / about 500g to about 2 minutes / about 500g (e.g., about 30 seconds / about 500g to about 1.5 minutes / about 500g, etc.). The speed of adding the core particles can be appropriately or appropriately adjusted to control the pH of the supernatant after the coating is completed, thereby inducing the effective formation of a substantially uniform Al-containing coating according to one or more embodiments. If the speed of adding the core particles is too fast, the pH of the supernatant can increase and become alkaline after the coating is completed, resulting in an uneven coating. In addition, if the speed of adding the core particles is too slow, the pH of the supernatant can decrease and become more acidic, also forming an uneven coating.
[0103] After all the core particles are added to the coating solution, stirring can be performed for about 15 minutes to about 60 minutes (e.g., about 20 minutes to about 50 minutes or about 30 minutes to about 45 minutes). The time from the beginning of adding the core particles to the coating solution to the completion of stirring, i.e., the coating reaction time, can be adjusted within about 1 hour.
[0104] In one or more embodiments, if (for example, when) the addition of the core particles to the coating solution and mixing are stopped, that is, the pH of the supernatant after the mixing or coating is completed may be in the range of about 5.5 to about 7.5. If the pH of the supernatant is less than about 5.5, the acidity becomes stronger, wherein a coating containing a fiber-shaped structure (for example, in the form of fibers, having a fibrous structure, etc.) may not be formed, and ultimately a substantially uniform Al-containing coating may not be formed. In addition, if the pH of the supernatant is greater than about 7.5, the alkalinity becomes stronger, wherein a coating containing a fiber-shaped structure (for example, in the form of fibers, having a fibrous structure, etc.) may not be formed, and a substantially uniform Al-containing coating may also be difficult to form.
[0105] After removing the aqueous solvent from the mixed solution, the resulting product can be dried, for example, at about 40°C to about 240°C, about 100°C to about 220°C, or about 150°C to about 200°C and, for example, under vacuum conditions, and a satisfactory coating product can be obtained under these conditions.
[0106] The dried product after removing the aqueous solvent from the mixed solution can be referred to as a coating product. The coating product may include a core particle and an Al-containing coating on the surface of the core particle, wherein the Al-containing coating may be in the form of a grid or spider web. This grid may be continuously formed over the entire surface of the core particle. The grid-like coating may wrap the core particle with a very thin and substantially uniform thickness to strengthen the surface of the positive electrode active material and improve structural stability, thereby enhancing high temperature and high voltage characteristics.
[0107] After mixing nickel-manganese composite hydroxide and lithium raw material, the heat treatment of the mixture can be referred to as the first heat treatment, and the heat treatment of the coated product can be referred to as the second heat treatment. The second heat treatment can be carried out in an oxygen atmosphere at a temperature range of about 700°C to about 850°C, about 750°C to about 840°C or about 800°C to about 830°C for about 2 hours to about 20 hours or about 3 hours to about 10 hours. In addition, the second heat treatment temperature can be lower than the first heat treatment temperature, and the second heat treatment time can be the same as the first heat treatment time or shorter than the first heat treatment time. By carrying out the second heat treatment under these conditions, a desired or appropriate coating can be obtained.
[0108] The obtained positive electrode active material includes: a core particle, including a layered lithium nickel manganese composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of total metals other than lithium in the layered lithium nickel manganese composite oxide; and a coating located on the surface of the core particle and including aluminum oxide, lithium aluminum oxide and / or a combination thereof (e.g., any appropriate one).
[0109] Positive electrode
[0110] In one or more embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material described above. In addition to the positive electrode active material described above, the positive electrode active material layer may further include other types (kinds) of positive electrode active materials. In addition, the positive electrode active material layer may optionally further include a binder, a conductive material and / or a combination thereof (e.g., any appropriate).
[0111] According to one or more embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2 . In addition, the density of the positive electrode active material layer in the final pressed positive electrode may be about 3.3 g / cc to about 3.7 g / cc, for example, about 3.3 g / cc to about 3.6 g / cc or about 3.4 g / cc to about 3.58 g / cc. If (for example, when) the positive electrode active material according to one or more embodiments is applied, it is appropriate or advantageous to implement such a loading level and density of the positive electrode active material layer, and the positive electrode in which the loading level and density of the positive electrode active material layer meet the above range is suitable for implementing a high-capacity, high-energy-density rechargeable lithium battery.
[0112] Binder
[0113] The binder improves the bonding properties of the positive electrode active material particles to each other and to the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin and nylon, but the present disclosure is not limited thereto.
[0114] Conductive Materials
[0115] A conductive material is included to provide electrode conductivity, and any suitable conductive material may be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and / or (e.g., any suitable) mixtures (e.g., combinations) thereof.
[0116] Each content (eg, amount) of the binder and the conductive material may be about 0.5 wt % to about 5 wt % based on 100 wt % of the positive electrode active material layer.
[0117] The positive electrode current collector may include an Al foil, but the present disclosure is not limited thereto.
[0118] Rechargeable lithium battery
[0119] According to some embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and electrolyte. As an example, a rechargeable lithium battery may include a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte.
[0120] According to the shape, the rechargeable lithium battery can be classified into a cylindrical battery, a prismatic battery, a pouch battery, a coin battery, etc. Figure 1 to Figure 4 is a schematic diagram showing a rechargeable lithium battery according to one or more embodiments, wherein Figure 1 For cylindrical batteries, Figure 2 is a prismatic cell, and Figure 3 and Figure 4 It is a pouch-shaped battery. Figure 1 to Figure 4 , the rechargeable lithium battery 100 includes: an electrode assembly 40 having a separator 30 disposed between a positive electrode 10 and a negative electrode 20; and a case 50 in which the electrode assembly 40 is accommodated. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte. Figure 1 As shown in , the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. Figure 2 In the embodiment, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3 and Figure 4 As shown in FIG. 1 , the rechargeable lithium battery 100 includes electrode tabs 70 , ie, a positive electrode tab 71 and a negative electrode tab 72 , serving as an electrical path for guiding current formed in the electrode assembly 40 to the outside.
[0121] The rechargeable lithium battery according to one or more embodiments may be rechargeable at a high voltage, and / or may be suitable for being driven at a high voltage. For example, the charging voltage of the rechargeable lithium battery may be greater than or equal to about 4.45V, about 4.45V to about 4.7V, about 4.45V to about 4.6V, or about 4.45V to about 4.55V. By applying the positive electrode active material according to one or more embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even (for example, when) charging at a high voltage, and can achieve high capacity and long cycle life characteristics.
[0122] Negative electrode
[0123] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and may further include a negative electrode active material, a binder, a conductive material, and / or (eg, any appropriate) combinations thereof.
[0124] Negative electrode active material
[0125] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.
[0126] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, and / or a combination thereof (e.g., any suitable combination) as a carbon-based negative electrode active material. The crystalline carbon may be natural graphite or artificial graphite in an amorphous or flaky, lamellar, spherical, or fibrous form (e.g., in the form of fibers). The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.
[0127] The lithium metal alloy includes an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0128] The material capable of doping / dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (0 < x ≤ 2), a Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and / or a combination thereof (e.g., any suitable combination), such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and / or a combination thereof (e.g., any suitable combination)) and / or a combination thereof (e.g., any suitable combination). The Sn-based negative electrode active material may be Sn, SnO x (0 < x ≤ 2, e.g., SnO2), a Sn alloy, and / or a combination thereof (e.g., any suitable combination).
[0129] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D 50 ) of the silicon-carbon composite particles may be, for example, about 0.5 μm to about 20 μm. According to one or more embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it may include secondary particles (cores) in which silicon primary particles are aggregated and an amorphous carbon coating (shell) on the surface of the secondary particles. The amorphous carbon may also be present between the silicon primary particles. For example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0130] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include: a core including crystalline carbon and silicon particles, and an amorphous carbon coating on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, and / or a combination thereof (e.g., any suitable combination). The amorphous carbon may include soft carbon, hard carbon, mesophase pitch carbonized product, and calcined coke.
[0131] If (e.g., when) the silicon-carbon composite includes silicon and amorphous carbon, then based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon may be about 10 wt% to about 50 wt%, and the content (e.g., amount) of amorphous carbon may be about 50 wt% to about 90 wt%. In one or more embodiments, if (e.g., when) the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, then based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon may be about 10 wt% to about 50 wt%, the content (e.g., amount) of crystalline carbon may be about 10 wt% to about 70 wt%, and the content (e.g., amount) of amorphous carbon may be about 20 wt% to about 40 wt%.
[0132] In one or more embodiments, the thickness of the amorphous carbon coating may be about 5 nm to about 100 nm. The average particle size (D 50 ) of the silicon particles (primary particles) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as silicon alone, in the form of a silicon alloy, or in the oxidized form of silicon. The oxidized form of silicon may be represented by SiO x (0 < x ≤ 2). At this time, the atomic content (e.g., amount) ratio of Si:O indicating the degree of oxidation may be about 99:1 to about 33:67. As used herein, if (e.g., when) no other definition is provided otherwise, the average particle size (D 50 ) indicates the diameter of the particles with a cumulative volume of about 50% by volume in the particle distribution.
[0133] The Si-based negative electrode active material or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. If (e.g., when) the Si-based negative electrode active material or the Sn-based negative electrode active material is mixed and used with the carbon-based negative electrode active material, the mixing ratio may be a weight ratio of about 1:99 to about 90:10.
[0134] Binder
[0135] The binder is used to bond (bond well) the negative electrode active material particles to each other, and is also used to bond the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, and / or a combination thereof (e.g., any suitable combination).
[0136] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, and / or (eg, any suitable) combinations thereof.
[0137] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol and / or (e.g., any suitable) combination thereof.
[0138] If (for example, when) an aqueous binder is used as a binder in the negative electrode active material layer, a cellulose compound capable of imparting viscosity may be further included. As the cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and alkali metal salts thereof may be mixed and used. The alkali metal may be Na, K or Li.
[0139] The dry binder may be a polymer material capable of becoming fibers (eg, in the form of fibers), and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, and / or (eg, any suitable) combinations thereof.
[0140] Conductive Materials
[0141] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and / or (e.g., any appropriate) mixtures thereof.
[0142] Based on 100wt% of the negative electrode active material layer, the content (e.g., amount) of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on 100wt% of the negative electrode active material layer, the content (e.g., amount) of the binder may be about 0.5wt% to about 5wt%. For example, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0wt% to about 5wt% of the conductive material.
[0143] current collector
[0144] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may be in the form of foil, sheet or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm or about 7 μm to about 10 μm.
[0145] Electrolyte
[0146] An electrolyte for a rechargeable lithium battery may include a non-aqueous organic solvent and a lithium salt.
[0147] The non-aqueous organic solvent is used as a medium for conveying (e.g., transporting) ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents and / or (e.g., any appropriate) combinations thereof.
[0148] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In one or more embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether group, etc.); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfone, etc.
[0149] The non-aqueous organic solvent may be used alone or as a mixture of two or more types (kinds), and if (for example, when) two or more types (kinds) are used as a mixture (when), the mixing ratio may be suitably or appropriately adjusted according to the desired or appropriate battery performance, which is well known to those skilled in the art.
[0150] If (for example, when) a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.
[0151] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0152] The electrolyte may further include vinyl ethylene carbonate, vinylene carbonate or ethylene carbonate-based compounds to improve the battery cycle life.
[0153] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0154] The lithium salt dissolved in the organic solvent supplies lithium ions in the battery, ensures the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are each independently an integer of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).
[0155] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. If (for example, when) the concentration of the lithium salt is within the above range, the electrolyte has suitable or appropriate ion conductivity and viscosity, and thus excellent or appropriate performance may be achieved, and lithium ions may be efficiently moved.
[0156] Diaphragm
[0157] Depending on the type or kind of the rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0158] The separator may include a porous substrate and a coating on one or both surfaces (eg, opposite surfaces) of the porous substrate, the coating including an organic material, an inorganic material, and / or (eg, any suitable) combination thereof.
[0159] The porous substrate may be a polymer film formed by: any one polymer selected from polyolefins (such as polyethylene and / or polypropylene), polyesters (such as polyethylene terephthalate and / or polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, and polytetrafluoroethylene (e.g., Teflon); or copolymers or mixtures of two or more thereof.
[0160] The porous substrate may have a thickness of about 1 micrometer (μm) to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0161] The organic material may include a (meth)acryl copolymer including: a first structural unit derived from (meth)acrylamide, and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or a salt thereof.
[0162] The inorganic material may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and (e.g., any suitable) combination thereof, but the present disclosure is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.
[0163] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.
[0164] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.
[0165] The following describes in more detail embodiments and comparative examples of the present disclosure. However, the following embodiments are merely examples of the present disclosure, and the present disclosure is not limited to the following embodiments.
[0166] Example 1
[0167] 1. Preparation of positive electrode active material
[0168] Ni 0.75 Mn0.23 Al 0.02 (OH)2 and LiOH were mixed in a molar ratio of 1:1.05, and then a first heat treatment was performed at 845°C for 8 hours in an oxygen atmosphere to prepare a quartz crystal having an average particle size (D 50 ) in the form of secondary particles with Li 1.05 Ni 0.75 Mn 0.23 Al 0.02 Lithium nickel manganese composite oxide with a composition of O2.
[0169] The residual lithium content of the prepared lithium nickel manganese composite oxide was measured by using an HCl titration method to calculate the content (e.g., amount) of each of Li2CO3 and LiOH from EP1 (equivalence point 1) and EP2 (equivalence point 2) according to the injection of HCl, and also calculate the total residual lithium content from the LiOH content and the Li2CO3 content. As a result, it was confirmed that the LiOH content was 4500ppm, the Li2CO3 content was 5500ppm, and the total residual lithium content was 2340ppm. Here, the unit of "ppm" refers to "10 - 4 wt%".
[0170] By adding 600g of distilled water and aluminum sulfate to 1L reactor, then stirring them (mixture) for about 5 minutes with about 350rpm to dissolve salt, to prepare coating solution.Confirm that the coating solution in which salt is completely dissolved is colorless and transparent.Under continuous stirring, 500g of lithium nickel manganese composite oxide is added to coating solution 1.5 minutes, then continue to stir for about 45 minutes.In this article, based on 100mol% of total metals other than lithium in final positive electrode active material, the aluminum content (for example, amount) in aluminum sulfate is designed to be 1.0mol%.If (for example, when) stirring is completed (time), the pH of its supernatant is 5.5.
[0171] After removing the solvent from the mixed solution with an aspirator and a filter press, the obtained coated product was dried by vacuum drying at 190°C.
[0172] The coated product was second heat-treated at 825° C. for 8 hours under an oxygen atmosphere to prepare a final positive electrode active material.
[0173] 2. Preparation of rechargeable lithium battery cells
[0174] Based on the total amount of the positive electrode active material layer slurry, 98.5wt% of the positive electrode active material, 1.0wt% of the polyvinylidene fluoride binder and 0.5wt% of the carbon nanotube conductive material were mixed to prepare the positive electrode active material layer slurry, and the positive electrode active material layer slurry was coated on an aluminum foil current collector, and then dried and pressed to prepare a positive electrode. At this time, the loading level of the positive electrode active material layer was 10mg / cm 2 , and the density of the positive electrode active material layer in the final pressed positive electrode was about 3.4 g / cc.
[0175] Based on the total weight of the negative electrode active material layer slurry, 97.5wt% of graphite negative electrode active material, 1.5wt% of carboxymethyl cellulose and 1wt% of styrene-butadiene rubber were mixed in an aqueous solvent to prepare a negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil current collector, and then dried and pressed to prepare a negative electrode.
[0176] A rechargeable lithium battery cell was prepared using a polytetrafluoroethylene separator and an electrolyte prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7 using a conventional method.
[0177] Example 2
[0178] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by adding the lithium nickel manganese type composite oxide to the coating solution at a high rate of about 1 minute (e.g., 500 g of the lithium nickel manganese type composite oxide was added to the coating solution for 1 minute instead of 1.5 minutes).
[0179] In Example 2, if (eg, when) coating is completed, the pH of the supernatant thereof is 6.5.
[0180] Example 3
[0181] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by adding the lithium nickel manganese type composite oxide to the coating solution at a high rate of about 30 seconds (e.g., 500 g of the lithium nickel manganese type composite oxide was added to the coating solution for 30 seconds instead of 1.5 minutes).
[0182] In Example 3, if (eg, when) coating is completed, the pH of the supernatant thereof is 7.5.
[0183] Comparative Example 1
[0184] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by using the lithium nickel manganese-based composite oxide of Example 1 and dry-coating alumina.
[0185] For example, Al coating is performed by mixing the lithium nickel manganese composite oxide of Example 1 with alumina powder, and then heat treating them at 825° C. for 8 hours in an oxygen atmosphere. Herein, the aluminum content (e.g., amount) in alumina is set to 1.0 mol% the same as in Example 1 based on 100 mol% of the total metals other than lithium in the final positive electrode active material.
[0186] Comparative Example 2
[0187] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that aluminum nitrate was used instead of aluminum sulfate and the lithium nickel manganese composite oxide was added to the coating solution at a high rate of about 1 minute (e.g., 500 g of the lithium nickel manganese composite oxide was added to the coating solution for 1 minute instead of 1.5 minutes).
[0188] For Comparative Example 2, if (eg, when) coating was completed, the pH of its supernatant was 8.5.
[0189] Comparative Example 3-1
[0190] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by adding the lithium nickel manganese type composite oxide to the coating solution at a slow rate of about 3 minutes (e.g., 500 g of the lithium nickel manganese type composite oxide was added to the coating solution for 3 minutes instead of 1.5 minutes).
[0191] For Comparative Example 3-1, if (eg, when) coating was completed, the pH of its supernatant was 4.5.
[0192] Comparative Example 3-2
[0193] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by adding the lithium nickel manganese type composite oxide to the coating solution at a high rate of about 5 seconds (e.g., 500 g of the lithium nickel manganese type composite oxide was added to the coating solution for 5 seconds instead of 1.5 minutes).
[0194] For Comparative Example 3-2, if (eg, when) coating was completed, the pH of its supernatant was 8.5.
[0195] Comparative Example 3-3
[0196] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 2, except that the positive electrode active material was prepared by the following post-addition method: a lithium nickel manganese composite oxide was first added to distilled water, and then aluminum sulfate was added thereto while the mixture was stirred, and the resulting mixture was then stirred for 45 minutes.
[0197] For Comparative Example 3-3, if (eg, when) coating was completed, the pH of its supernatant was 6.5.
[0198] Example 4
[0199] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the first heat treatment was performed at 855° C. The lithium nickel manganese-based composite oxide of Example 4 had a LiOH content (e.g., amount) of 4000 ppm, a Li2CO3 content (e.g., amount) of 3000 ppm, and a total residual lithium content (e.g., amount) of 1720 ppm on the surface of the secondary particles.
[0200] For Example 4, if (eg, when) coating is completed, the pH of the supernatant is 6.5.
[0201] Comparative Example 4
[0202] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 2, except that a positive electrode active material having an average particle size (D 50 ) in the form of secondary particles having LiNi 0.945 Co 0.04 Al 0.015 The positive electrode active material is prepared by using a lithium nickel cobalt aluminum composite oxide with a composition of O2, rather than a lithium nickel manganese composite oxide. The lithium nickel cobalt aluminum composite oxide of Comparative Example 4 has a LiOH content (e.g., amount) of 6000 ppm, a Li2CO3 content (e.g., amount) of 7000 ppm, and a total residual lithium content (e.g., amount) of 3060 ppm on the surface of the secondary particles.
[0203] For Comparative Example 4, the pH of the supernatant thereof was 12 if (eg, when) the coating was completed.
[0204] Comparative Example 5
[0205] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 2, except that a positive electrode active material having an average particle size (D 50) in the form of secondary particles of LiCoO2, rather than a lithium nickel manganese composite oxide, to prepare a positive electrode active material. The lithium cobalt oxide of Comparative Example 5 has a LiOH content (e.g., amount) of 850 ppm, a Li2CO3 content (e.g., amount) of 230 ppm, and a total residual lithium content (e.g., amount) of 290 ppm on the surface of the secondary particles.
[0206] For Comparative Example 5, if (eg, when) coating was completed, the pH of its supernatant was 3.5.
[0207] For better understanding, the design details of the embodiments and comparative examples are shown in Table 1.
[0208] (Table 1)
[0209]
[0210] Evaluation Example 1: Coating Quality Evaluation by SEM and EDS-Mapping
[0211] Figure 5 : is a SEM image showing the surface of the coating product dried after coating in Example 1. Figure 6 for Figure 5 A magnified image of the image. Figure 5 and Figure 6 , on the surface of the secondary particle of Example 1, the Al-containing coating layer was formed in the form of a grid or spider web containing a fiber-shaped structure (eg, in the form of fibers, having a fibrous structure, etc.).
[0212] Figure 7 : is an EDS analysis image showing a cross section obtained by cutting the final positive electrode active material of Example 1. Figure 7 , on the surface of the secondary particle of Example 1, the Al-containing coating layer was formed to have a uniform (eg, substantially uniform) thickness.
[0213] Figure 8 is a SEM image of the surface of the coating product of Example 2, Fig. 9 is a SEM image of the surface of the coating product of Example 3, and Fig.10 This is a SEM image of the surface of the coated product of Example 4. Figure 8 to Figure 10 The embodiments in which the pH of the supernatant after coating was in the range of 5.5 to 7.5 showed that the Al-containing coating in the form of a grid or spider web was uniformly (eg, substantially uniformly) formed on the surface of the positive electrode active material.
[0214] Fig.11 This is an EDS analysis image showing a cross section of the positive electrode active material of Comparative Example 1, in which Al is highlighted. Fig.11 , Comparative Example 1 to which dry coating was applied showed that the Al-containing coating layer was not uniformly formed.
[0215] Fig.12 : is a SEM image showing the surface of the coating product of Comparative Example 2. Fig.12 , Comparative Example 2 using aluminum nitrate as a coating raw material showed that an uneven Al-containing coating layer was formed on the surface of the secondary particles.
[0216] Fig.13 The SEM image of the surface of the coating product of Comparative Example 3-1 is shown. Fig.13 , Comparative Example 3-1, which used aluminum sulfate as a coating raw material and whose supernatant after coating was strongly acidic at a pH level of 4.5, showed that a non-uniform Al-containing coating was formed, and no grid-like coating was observed.
[0217] Fig.14 This is a SEM image of the surface of the coating product of Comparative Example 3-2. Fig.14 , Comparative Example 3-2, which used aluminum sulfate as a coating raw material and whose supernatant was alkaline at pH 8.5, showed that a non-uniform Al-containing coating was formed, and no grid-like coating was observed.
[0218] Fig.15 : is a SEM image showing the surface of the coated product of Comparative Example 3-3. Comparative Example 3-3 (in which coating was performed by the post-addition method) showed that an uneven Al-containing coating was formed.
[0219] Fig.16 : is a SEM image showing the surface of the coating product of Comparative Example 4. Fig.17 For Comparative Example 4 using a layered lithium nickel cobalt aluminum-based composite oxide leaving a residual lithium content (e.g., amount) of 3000 ppm or more on the surface instead of the layered lithium nickel manganese-based composite oxide of one or more embodiments, even when the coating method of one or more embodiments was applied, an uneven Al-containing coating was formed and no grid shape was observed.
[0220] Fig.17 : is a SEM image showing the surface of the coating product of Comparative Example 5. Fig.17 For Comparative Example 5, which uses a lithium cobalt-based oxide leaving a small residual lithium content (e.g., amount) on the surface instead of the layered lithium nickel manganese-based composite oxide of one or more embodiments, an uneven Al-containing coating is formed even when the coating method of one or more embodiments is applied thereto.
[0221] Evaluation Example 2: EP-EDS Analysis
[0222] EP-EDS analysis was performed on the coated products of Examples 1 to 3 and Comparative Examples 1, 2 and 3-3 to calculate the ratio of the Al content (e.g., amount) (at%, atomic percentage) on the particle surface to the total content (e.g., amount) of Ni, Mn and Al of 100at% (Al / (Ni+Mn+Al)), and the results were given in Table 1. Fig.18 EP-EDS is an analytical method for measuring the concentration of a specific element at a specific depth by irradiating an electron beam on the surface of a target material. The depth can be controlled by changing the accelerating voltage of the electron beam. In this evaluation example, EP-EDS was performed using a Helios G4 HX from Thermo Fisher at 3 kV and 0.8 nA.
[0223] refer to Fig.18 , Comparative Example 1 applying dry coating showed the lowest Al content (e.g., amount) on the surface, Comparative Example 2 applying aluminum nitrate as the coating raw material, and Comparative Examples 3-3 applying the post-addition method each showed a lower Al content (e.g., amount) on the surface than Examples 1 to 3.
[0224] The Examples each exhibited a higher Al content (eg, amount) ratio of about 45% to 55% relative to the total metal content (eg, amount) other than lithium on the surface of the positive electrode active material particles, compared to the Comparative Examples.
[0225] In the context of the present application, unless otherwise defined, the terms "use", "using" and "used" may be regarded as synonymous with the terms "utilize", "utilizing" and "utilized", respectively.
[0226] When describing embodiments of the present inventive concepts, the use of “may” refers to “one or more embodiments of the present inventive concepts”.
[0227] As used herein, the term "about" and similar terms are used as terms of approximation rather than as terms of degree, and are intended to account for the inherent deviations in measured or calculated values that will be recognized by one of ordinary skill in the art. "About" as used herein includes the stated value and means within an acceptable range of deviations of the particular value determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (e.g., limitations of the measurement system). For example, "about" may mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.
[0228] Furthermore, any numerical range set forth herein is intended to include all sub-ranges of the same numerical precision falling within the set forth range. For example, the range of "1.0-10.0" is intended to include between the set forth minimum value 1.0 and the set forth maximum value 10.0 (including 1.0 and 10.0), that is, all sub-ranges (such as, for example, 2.4-7.6) having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0. Any maximum numerical limit set forth herein is intended to include all lower numerical limits falling therein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits falling therein. Accordingly, the applicant reserves the right to modify this specification (including claims) to explicitly set forth any sub-range falling within the range explicitly set forth herein.
[0229] The battery management system (BMS) device and / or any other related device or component according to the embodiments of the present invention described herein may be implemented using any appropriate hardware, firmware (e.g., a dedicated integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on a separate IC chip. Further, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), or a printed circuit board (PCB), or formed on a substrate. Further, the various components of the device may be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components to perform the various functions described herein. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device (such as, for example, a random access memory (RAM)). The computer program instructions may also be stored in other non-temporary computer-readable media (such as, for example, a CD-ROM, a flash drive, etc.). Moreover, those skilled in the art should recognize that, without departing from the scope of the present disclosure, the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a particular computing device may be distributed on one or more other computing devices.
[0230] Although the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it should be understood that the present disclosure should not be limited to the disclosed embodiments, but rather is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.
Claims
1. A positive electrode active material comprising: a plurality of core particles including a layered lithium nickel manganese-based composite oxide having a nickel content of greater than or equal to 60 mol % based on 100 mol % of total metals other than lithium in the layered lithium nickel manganese-based composite oxide, and a coating on the surface of the core particle and comprising aluminum, wherein the amount of Al in the coating layer is 0.5 mol% to 1.5 mol% based on 100 mol% of the total metals except lithium in the positive electrode active material, and The coating includes a fibrous structure.
2. The positive electrode active material according to claim 1, wherein The coating is in the form of a grid or spider web.
3. The positive electrode active material according to claim 1, wherein The coating layer continuously exists on the surface of the core particle.
4. The positive electrode active material according to claim 1, wherein The thickness of the coating is 5nm to 200nm; and / or The thickness of the coating layer within one positive electrode active material particle has a deviation of less than or equal to 20%.
5. The positive electrode active material according to claim 1, wherein The coating includes a layered aluminum compound.
6. The positive electrode active material according to claim 1, wherein The coating includes aluminum oxide, lithium aluminum oxide, or a combination thereof.
7. The positive electrode active material according to claim 1, wherein The coating includes LiAlO2.
8. The positive electrode active material according to claim 1, wherein The amount of Al is 45 to 55 at % based on 100 at % of total metals excluding lithium on the surface of the positive electrode active material as measured on the surface of the positive electrode active material by energy distribution energy dispersive X-ray spectroscopy.
9. The positive electrode active material according to claim 1, wherein In the layered lithium nickel manganese composite oxide, the amount of nickel is 60 mol% to 80 mol% based on 100 mol% of the total metals excluding lithium in the layered lithium nickel manganese composite oxide, and the amount of manganese is greater than or equal to 10 mol% based on 100 mol% of the total metals excluding lithium in the layered lithium nickel manganese composite oxide.
10. The positive electrode active material according to claim 1, wherein The layered lithium nickel manganese-based composite oxide further includes aluminum, and an amount of the aluminum in the core particle is greater than 0 mol % and less than or equal to 3 mol % based on 100 mol % of the total metals except lithium in the layered lithium nickel manganese-based composite oxide.
11. The positive electrode active material according to claim 1, wherein In the layered lithium nickel manganese-based composite oxide, an amount of cobalt is 0 mol% to 0.01 mol% based on 100 mol% of the total metals except lithium in the layered lithium nickel manganese-based composite oxide.
12. The positive electrode active material according to claim 1, wherein The layered lithium nickel manganese composite oxide is represented by Chemical Formula 1: Chemical formula 1 Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 Wherein in Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.
13. The positive electrode active material according to claim 1, wherein The core particles are secondary particles each formed by aggregating a plurality of primary particles, and The positive electrode active material further includes a grain boundary coating portion including Al and located on a surface of the primary particle inside the secondary particle; and in The amount of Al in the grain boundary coating portion is less than the amount of Al in the coating layer.
14. The positive electrode active material according to claim 1, wherein The positive electrode active material is in the form of particles, and the particles have an average particle size D of 10 μm to 25 μm. 50 .
15. A method for preparing a positive electrode active material, the method comprising: preparing a core particle comprising a layered lithium nickel manganese-based composite oxide having a nickel content of greater than or equal to 60 mol % based on 100 mol % of total metals other than lithium in the layered lithium nickel manganese-based composite oxide and having a residual lithium content of 0.15 wt % to 0.25 wt % on the surface of the core particle, Aluminum sulfate is added to an aqueous solvent and mixed to prepare a coating solution, adding the core particles to the coating solution and mixing to prepare a mixed solution having a pH of 5.5 to 7.5, and The aqueous solvent is removed from the mixed solution, and the resultant is dried and heat-treated to obtain the positive electrode active material.
16. The method of claim 15, wherein In the layered lithium nickel manganese composite oxide, based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese composite oxide, the nickel content is 60 mol% to 80 mol%, the manganese content is greater than or equal to 10 mol%, the aluminum content is greater than 0 mol% and less than or equal to 3 mol%, and the cobalt content is 0 mol% to 0.01 mol%; and / or in Based on 100 wt% of the core particles, The content of LiOH remaining on the surface of the core particle is 0.3 wt % to 0.5 wt %, and The content of Li2CO3 remaining on the surface of the core particle is 0.25wt% to 0.6wt%; and / or in The content of aluminum derived from the aluminum sulfate is 0.5 mol % to 1.5 mol % based on the sum of 100 mol % of the total metals except lithium in the core particles and aluminum of the aluminum sulfate.
17. The method of claim 15, wherein The duration of adding the aluminum sulfate and mixing is 1 minute to 60 minutes, and the mixing speed is 100 rpm to 800 rpm; and / or in The coating solution is colorless and transparent and has a pH of 1.5 to 3.5; and / or in The core particles are added to the coating solution at a speed of 30 seconds / 500 g to 2 minutes / 500 g, The mixing time after adding the core particles to the coating solution is 15 minutes to 60 minutes, and The pH of the supernatant after the mixing is 5.5-7.
5.
18. The method of claim 15, wherein After removing the aqueous solvent from the mixed solution, the drying of the obtained product is carried out at 40° C. to 240° C. under vacuum conditions; and / or in The positive electrode active material obtained by removing the aqueous solvent from the mixed solution and drying the resulting product includes core particles and an Al-containing coating layer located on the surface of the core particles, and the Al-containing coating layer is in the form of a grid or a spider web; and / or in The heat treatment is carried out at 700°C to 850°C; and / or The positive electrode active material comprises: the core particle, and A coating layer is located on the surface of the core particle and includes aluminum oxide, lithium aluminum oxide, or a combination thereof.
19. A positive electrode comprising: a positive electrode current collector, and A positive electrode active material layer, on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 14 or the positive electrode active material prepared by the method according to any one of claims 15 to 18, in The positive electrode active material layer has a 10 mg / cm 2 ~40mg / cm 2 load level; and / or The positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.
20. A rechargeable lithium battery comprising: The positive electrode according to claim 19, negative electrode, and Electrolyte, in The charging voltage of the rechargeable lithium battery is greater than or equal to 4.45V.